2006
DOI: 10.1111/j.1467-9221.2006.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Group Identification under Conditions of Threat: College Students' Attachment to Country, Family, Ethnicity, Religion, and University Before and After September 11, 2001

Abstract: Three classes of introductory psychology students at the University of Pennsylvania completed a survey including several measures of group identification on 20 March 2001, 15 September 2001, and 24 March 2003. Importance of country and university were rated higher four days after the 9/11 terrorist attacks than six months before or 18 months after. Scores on a 9‐item scale of identification with country were higher immediately after 9/11 than at the other two assessments. Four theories (group dynamics, CORFing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 47 publications
2
56
0
3
Order By: Relevance
“…The absence of an increase in attachment to the principle of laïcité just after the attacks is surprising given the political and media discourse during this period (Moliner, 2015). This result suggests that the principle of laïcité is not sufficiently clear and important to French people and that it is not linked to identification with the ingroup (Moskalenko et al, 2006). Although the decrease in attachment to the principle of laïcité during the third data collection period is difficult to interpret, the change in the relation between SDO and attachment to laïcité over the three data collection periods provides a number of clues to the processes involved.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The absence of an increase in attachment to the principle of laïcité just after the attacks is surprising given the political and media discourse during this period (Moliner, 2015). This result suggests that the principle of laïcité is not sufficiently clear and important to French people and that it is not linked to identification with the ingroup (Moskalenko et al, 2006). Although the decrease in attachment to the principle of laïcité during the third data collection period is difficult to interpret, the change in the relation between SDO and attachment to laïcité over the three data collection periods provides a number of clues to the processes involved.…”
Section: Discussionmentioning
confidence: 90%
“…These authors suggest that one of the effects of this activation is to increase an individual's attachment to the values of their ingroup. Similarly, Moskalenko, McCauley, and Rozin (2006) found that after September 11, 2001, individuals were more strongly attached to and identified more strongly with their ingroup. Finally, such events engender more negative attitudes towards people/groups seen as embracing opposing norms and values to those of the ingroup (Greenberg, Pyszczynski, & Solomon, 1986).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In the 2 months after September 11, respondents answering an Internet survey endorsed a number of character strengths more strongly, including gratitude, hope, kindness, leadership, love, spirituality, and teamwork (Peterson & Seligman, 2003). Four days after the attacks, college students in Pennsylvania showed a temporary increase in identification with their country that was no longer present 18 months later (Moskalenko, McCauley, & Rozin, 2006). They also showed a temporary increased rating of the importance of their country and their university.…”
Section: Attitudes and Behaviormentioning
confidence: 99%
“…However, Witteborn's study of Arab collective identities in post 9/11 USA and Moskalenko et al's study of college students suggest that identity labels and groupings are themselves subject to change and shifting in such circumstances (Moskalenko, McCauley, & Rozin, 2006;Witteborn, 2007). Moreover, the effect of inter-group contact over a long period in a society such as contemporary Britain is under-investigated and so it is less clear what we might expect in terms of stability or fragility of inter-group connections.…”
Section: Terrorism Increased Uncertainty and Social Identitymentioning
confidence: 99%